Production-distribution model considering traceability and carbon emission: A case study of the Indonesian canned fish food industry - Dwi Iryaning Handayani; Ilyas Masudin; Ahmad Rusdiansyah; Judi Suharsono (Logistics, 2021)
Background: Traceability systems and carbon emissions are two important factors involved in production and distribution activities. The involvement of these two factors in production and distribution activities along the supply chain will ensure the safety and quality of food through the manufacture, packaging and distribution of products with minimal costs and in an environmentally friendly way. Objective: This study aimed to develop a model of canned fish food production and distribution integration by considering traceability and carbon emissions to minimize total costs. Method: A mixed-integer linear programming (MILP) approach was used to develop mathematical models and the optimal solution of the model created was obtained using an open-source spreadsheet solver program. Results: The results show that the proposed models produce the minimum total production and distribution cost with high traceability and low carbon emissions. Conclusions: The sensitivity analysis from this study shows that there is a significant relationship between production, carbon emissions, and the total cost of production-distribution. Moreover, it was concluded that the production level, carbon emission level, and emission threshold can have a significant influence in the generation of the total carbon emissions.
Keywords: 650; carbon emission; integration production-distribution; MILP; traceability; Fischverarbeitung; Vertrieb; Treibhausgas-Emissionen; Lebensmittelsicherheit; Ganzzahlige Optimierung; Lineare Optimierung; Indonesien